RETRACTED: Transport system and transport education development: Some challenges and opportunities - Nadtochiy Yulia; Mikaeva Anzhela (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001